Perbandingan antara Teknologi dan Peforma pada Komputasi Awan (Cloud Computing) - Nadya Apriliani; Arief Riski Indra Pratama; Agung Susilo Yuda Irawan (Infotek: Jurnal Informatika dan Teknologi, 2022)
Cloud computing is the best method used for data utilization and organization. Cloud provides resources for humans through the internet. There are many technologies in cloud systems, each using a different type of protocol and method. Multiple tasks can be executed on different servers per second, which cannot be executed on the user's computer. In this study, a systematic review is used which provides information related to the most frequently used techniques or technologies. The most popular technologies used in cloud systems are Hadoop, Dryad and other frameworks. Apart from that, there are many tools used to optimize cloud system performance, such as Cap3, HEP and Cloudburst. This study also reviews in detail about the system in cloud computing, the technology used and the best technology used according to several factors and criteria such as procedure costs, speed cons and prospects. In addition, a comprehensive comparison of the tools used for system utilization in cloud computing is presented.